Ground Anoles (Anolis humilis) Discriminate between Aposematic and Cryptic Model Insects - Baruch, Ethan M. (2016)
Aposematic coloration allows predators to use visual cues to avoid eating potentially toxic or distasteful prey. Predators across many animal taxa actively avoid aposematically colored prey and remember distasteful brightly colored prey longer than cryptically colored prey. Lizards of many species are known to use aposematic coloration when foraging; however, most previous studies investigating the recognition of aposematic coloration by lizards have used live prey. This factor makes it difficult to determine whether lizards rely solely on visual cues or use a combination of sensory cues in prey selection. To determine whether anoles can select prey relying on only visual cues, we investigated the foraging response of Ground Anoles (Anolis humilis) to aposematic prey. By using clay models, we were able to remove any natural olfactory or behavioral cues that lizards may use in prey selection. We presented anoles with aposematically and cryptically colored insect models and found that lizards recognized and avoided aposematic models. This study demonstrates that A. humilis are able to use visual cues alone when selecting prey items. Our findings support previous work demonstrating that aposematic coloration is advantageous for prey, as it decreases the risk of attack by predators. The coloration also benefits predators, as they are able to recognize aposematic prey by sight alone, and avoid expending energy on an unpalatable meal.